Pengaruh Dewan Komisaris Independen, Ukuran Perusahaan Dan Profitabilitas Terhadap Pengungkapan Risiko Perusahaan Food And Beverage Di BEI - Gina Septiana; Mike Kusuma Dewi; Elsa Meirina (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2023)
Risk disclosure is a type of risk that companies use in presenting risk information that comes in operating business activities in the financial statements for one period. The company must present risk information and disclose it clearly and accurately.This study aims to test the independent board of commissioners, company size and profitability on corporate risk disclosures in the food and beverage sector on the IDX. This study uses a sample in the food and beverage sector on the IDX in 2019-2021. Based on positive sampling, the number of food and beverage companies used in this study were 12 companies. Hypothesis testing uses panel data regression using the E Views 8.0 program. The results of this study indicate that the independent board of commissioners has a significant negative effect on risk disclosure, firm size has no effect on risk disclosure and profitability has no effect on risk disclosure.